'Saying yes when you need to and no when you need to' an interpretative phenomenological analysis on coaches' well-being. Issue 1 (2nd January 2023) - McEwen, Deb; Rowson, Tatiana
ABSTRACT : How coaches both experience and lead their own well-being has an important role to play in coaching; however, coaches' individual well-being has gained less attention in training, discourse, or research to date. This paper intends to amend this deficit and provides an understanding and conceptual model of the dynamics in a coach's individual well-being at work. Semi-structured interviews were carried out with 18 coaches and the findings illustrate that Coaches' well-being is not a static state. There are job demands of coaching that can impact a coach's well-being and there is a need for coaches to balance their resources with a high level of agility. There are also deeper underlying dynamics to a coach's well-being that are interrelated with each other; energy currents, self-regulation, and levels of well-being. The way in which coaches optimise their resources and energy and active management of self will help or hinder a coach's well-being at work, which may be more difficult for novice coaches.